Khilafatul Muslimin: Analisis tentang Deradikalisasi Diri Gerakan Fundamentalis Indonesia - Khairinnas, Khairinnas (Jurnal Sosiologi Dialektika Sosial, 2023)
This research article aims to analyze the case of Khilafatul Muslimin, a conservative Islamic movement in Indonesia, as an example of religious fundamentalism and self-deradicalization. Khilafatul Muslimin has been active since 1997 and has expressed its support for Pancasila and the Unitary State of the Republic of Indonesia. The article argues that Khilafatul Muslimin is undergoing a process of self-deradicalization to prevent its members, most of whom come from Muslim families, from committing acts of violence in the name of religion. This article also examines the previous theoretical framework of religious fundamentalism and its relationship to violence and modernity in the Indonesian context. The article suggests that the government, especially the National Counterterrorism Agency (BNPT), exploit the potential of Khilafatul Muslimin. The process of self-deradicalization of Muslims is a process that aims to change the attitudes and behavior of Muslims who are involved in extreme violence or religious radicalism.Artikel ini bertujuan untuk menganalisis kasus Khilafatul Muslimin, sebuah gerakan konservatif Islam di Indonesia, sebagai contoh fundamentalisme agama dan deradikalisasi diri. Khilafatul Muslimin aktif sejak tahun 1997 dan menyatakan dukungannya terhadap Pancasila dan Negara Kesatuan Republik Indonesia. Artikel tersebut berpendapat bahwa Khilafatul Muslimin mengalami proses deradikalisasi diri untuk mencegah anggotanya yang sebagian besar berasal dari keluarga Muslim melakukan aksi kekerasan atas nama agama. Artikel ini juga mengkaji kerangka teoritis fundamentalisme agama sebelumnya dan kaitannya dengan kekerasan dan modernitas dalam konteks Indonesia. Artikel tersebut menyarankan agar pemerintah khususnya Badan Nasional Penanggulangan Terorisme (BNPT) memanfaatkan potensi Khilafatul Muslimin. Proses deradikalisasi diri Muslimin adalah proses yang bertujuan untuk mengubah sikap dan perilaku Muslimin yang terlibat dalam kekerasan ekstrem atau radikalisme agama.